Analysis of TFGBR1*6A variant in individuals evaluated for Marfan syndrome. Issue 7 (26th April 2016) - Somers, Allyson E.; Hinton, Robert B.; Pilipenko, Valentina; Miller, Erin; Ware, Stephanie M.
Abstract : Marfan syndrome (MFS) and Loeys–Dietz syndrome (LDS) are genetic disorders that affect connective tissue as a result of dysregulated TGF‐β signaling. MFS is most frequently caused by mutations in FBN1 whereas Loeys–Dietz syndrome results from mutations in TGFBR1 or TGFBR2 . There is substantial inter‐ and intra‐familial phenotypic variability among these disorders, suggesting the presence of genetic modifiers. Previously, a polymorphism in the TGFβR1 protein termed the TFGBR1*6A allele was found to be overrepresented in patients with MFS and was identified as a low penetrance allele with suggestion as a possible modifier. To further investigate the importance of this variant, a retrospective review of genetic and phenotypic findings was conducted for 335 patients evaluated for suspicion of MFS or related disorders. In patients with a diagnosis of MFS, the presence of the TFGBR1*6A allele was not associated with phenotypic differences. Similarly, careful phenotyping of patients who carried the TFGBR1*6A allele but did not have MFS did not identify an altered frequency of specific connective tissue features. In this small cohort, the results did not reach significance to identify the TFGBR1*6A allele as a major modifier for aortic dilation, ectopia lentis, or systemic features associated with MFS or other connective tissue disorders. © 2016 Wiley Periodicals, Inc.